Powering Sensors in IoT System by Using Compact Seven Band PIFA Rectenna - Nermeen A. Eltresy; Dalia M. Elsheakh; Esmat A. Abdallah; Hadia M. Elhennawy (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A compact seven band coplanar waveguide fed planar inverted F antenna (PIFA) is presented. The proposed antenna is designed to harvest the ambient radio frequency energy at GSM 900, GSM 1800, LTE band 11 and 7, UMTS 2100, Wi-Fi 2.4, LTE and WIMAX 5.2. The antenna is simulated using 3D electromagnetic simulators CST and HFSS. Moreover, the antenna is fabricated and it is used to measure the indoor RF spectrum in Egypt. A simple AC to DC converter unit is designed by using HSMS 2850 Schottky diode to convert the collected RF energy to DC energy. The antenna and the AC to DC converter are integrated to form the RF energy harvesting system. The maximum measured efficiency obtained at 2.4 GHz is about 63.7%.